TOURISM AMBASSADORS AS SPECIAL DESTINATION IMAGE INDUCERS - Morand, Jean-Claude; Cardoso, Lucília; Pereira, Alexandra Matos; Araújo-Vila, Noelia; Almeida, Giovana Goretti Feijó de (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2021)
The image of destinations is a key factor when it comes to positioning and attracting the attention and interest of potential tourists. That being, the subject matter is relevant to experts and academics as well as destination managers looking for new alternatives to generate greater impact and influence. Today, the use of information and communication technologies (ICT) is widespread in all areas of life, being also useful and fully adopted in tourism image projections, mainly through social networks. Accordingly, this article focuses on the figure of the tourism ambassador as a diffuser or enhancer of the image of a tourism destination, particularly through the use of an appropriate web platform created by the French tourism destination authority—the Ambassadeurs Savoie Mont Blanc. To understand the repercussions of this initiative, a content analysis of its official Facebook page is made, studying variables such as fans, content and engagement.